2015
DOI: 10.1007/978-3-319-16919-4_29
|View full text |Cite
|
Sign up to set email alerts
|

Use of Bone Marrow-Derived Mesenchymal Stem Cells in Improving Thioacetamide Induced Liver Fibrosis in Rats

Abstract: Liver fibrosis, is one of big problems usually ends with cirrhosis which considered a life threatening disease as the only way of treatment is the liver transplantation, this study aimed to find a new way for fibrosis treatment by the use of bone marrow isolated Mesenchymal stem cells (MSCs). Thioacetamide (TAA) was used for fibrosis induction in male Sprague Dawely (SD) rats which divided into two random groups: group infused with TAA for fibrosis induction and group as control negative group. MSCs were isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
3
0
0
Order By: Relevance
“…The hepatic tissue preserved it is nearly normal hepatic lobular architecture with central veins and radiating hepatic cords. This results came in agreement with previous studies (Ahmed et al, 2014, Volarevic et al, 2014and Mansour et al, 2015 who found that MSCs could reduce the proliferation of stellate cells and collagen type I synthesis through the secretion of IL-10, and to promote hepatic stellate cell apoptosis through the secretion of HGF and NGF lead to a significant decrease in collagen deposition and proliferation. MSCs can exert antifibrotic effect in liver cirrhosis through the expression of matrix metalloproteinase-9 (MMP-9) that degrades the Moreover, the portal areas showed severe congestion of the portal blood vessels with mild vasculitis, multiple thrombosis and perivascular edema as well as perivascular mononuclear leucocytic infiltration.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The hepatic tissue preserved it is nearly normal hepatic lobular architecture with central veins and radiating hepatic cords. This results came in agreement with previous studies (Ahmed et al, 2014, Volarevic et al, 2014and Mansour et al, 2015 who found that MSCs could reduce the proliferation of stellate cells and collagen type I synthesis through the secretion of IL-10, and to promote hepatic stellate cell apoptosis through the secretion of HGF and NGF lead to a significant decrease in collagen deposition and proliferation. MSCs can exert antifibrotic effect in liver cirrhosis through the expression of matrix metalloproteinase-9 (MMP-9) that degrades the Moreover, the portal areas showed severe congestion of the portal blood vessels with mild vasculitis, multiple thrombosis and perivascular edema as well as perivascular mononuclear leucocytic infiltration.…”
Section: Discussionsupporting
confidence: 93%
“…Homing of the injected MSCs into the liver tissue was confirmed by fluorescent technique (labeled MSCs with the PKH26 dye). These finding agreed with the results of Liu et al, (2009), El-khayat et al, (2013b and Mansour et al, (2015) who found that homing of MSCs into liver tissue was confirmed by labeled MSCs with the PKH26 dye, these cells showed strong red auto fluorescence after transplantation into rats, confirming that these cells were actually seeded into the liver tissue.…”
Section: Discussionsupporting
confidence: 91%
“…The heavy proliferation of fibrous connective tissues that form fibrous bridges connecting portal regions led to the formation of a pseudo cleavage that separates the hepatic lobe from the other lobules. These findings were agreed with other results (Hessin et al, 2015), meanwhile, after MSCs treatment there were thin strands of fibrous connective tissue between the hepatic lobules (Rabani et al, 2010, Volarevic et al, 2014and Mansour et al, 2015. All found that MSCs could reduce the proliferation of stellate cells and collagen synthesis and promote hepatic stellate cell apoptosis through the secretion of HGF and NGF, Thus, this leads to a significant decrease in collagen deposition.…”
Section: Discussionsupporting
confidence: 91%